One-stage surgical excision of a huge bilateral multiple osteochondroma of the hip: a case report - Taheriazam, Afshin (Electron Physician, 2017)
Osteochondroma or hereditary multiple exostoses is the most common benign bone tumor and is usually found in young patients. Osteochondromata of the proximal femur or hip have been reported in 30% to 90% of patients with hereditary multiple exostoses. This article presents a 25-year-old-male referred to our orthopedic clinic with a complaint of pain in both groins for the last four years which has deteriorated in the past 6 months by limitation of range of motion. Radiographic findings were consistent with huge hip osteochondroma and a histopathological report confirmed the diagnosis. This was a case of a huge bilateral osteochondroma of the hip originating from the posterior of the hips to the neck of the femur and hip joints and part of proximal of femur, that underwent one-stage surgical excision of the tumor with posterior approach and tumor resection. As we know, this case of bilateral huge hip osteochondromas has rarely been presented previously by someone who has undergone one-stage surgery treatment of a tumor this size. Bilateral hip osteochondroma is a rare condition and we showed that one-stage excision can be performed successfully.